2021
DOI: 10.1590/0047-2085000000315
|View full text |Cite
|
Sign up to set email alerts
|

Saúde mental dos estudantes de Medicina do Brasil durante a pandemia da coronavirus disease 2019

Abstract: RESUMO Objetivo: O objetivo desta pesquisa é verificar a prevalência de sintomas de sofrimento psíquico em estudantes do curso de Medicina durante a pandemia da COVID-19. Métodos: Trata-se de um estudo transversal e exploratório que avaliou 656 estudantes do curso de Medicina do Brasil. Os dados foram coletados, em maio e junho de 2020, por meio de dois instrumentos autoaplicáveis. O primeiro foi um questionário elaborado pelos próprios autores para avaliar o perfil social, demográfico e cultural da populaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
1
36

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 18 publications
(17 reference statements)
3
18
1
36
Order By: Relevance
“…Similar to our findings, previous research has shown the increased risk of mental health problems among university students with low social support during the new coronavirus pandemic [44,[48][49][50]. Feelings of loneliness and poor perception of family environment resulted in psychological distress during the pandemic [49].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to our findings, previous research has shown the increased risk of mental health problems among university students with low social support during the new coronavirus pandemic [44,[48][49][50]. Feelings of loneliness and poor perception of family environment resulted in psychological distress during the pandemic [49].…”
Section: Discussionsupporting
confidence: 89%
“…Remote online teaching can be considered a source of stress among university students during pandemic [44,61]. For instance, difficulties in adapting to online teaching was associated with psychological distress among medical students [44]. However, our study indicated the offer of online teaching during the social distancing period contributed to the reduction of student's psychological suffering.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations